UMP Womens Association donates RM10,000 to Yayasan UMP Fund to help the needful - Nor Salwana, Mohammad Idris (2022)
KUANTAN, 31 December 2021 – The Universiti Malaysia Pahang Women’s Association (MATAHARI) has submitted a donation of RM10,000 to Yayasan UMP to support its fundraising efforts for the Fund and Endowment to help students and people in need.